2018
DOI: 10.1002/biot.201700733
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion Cell Culture Decreases Process and Product Heterogeneity in a Head‐to‐Head Comparison With Fed‐Batch

Abstract: In this study, the authors compared the impacts of fed-batch and perfusion platforms on process and product attributes for IgG1- and IgG4-producing cell lines. A "plug-and-play" approach is applied to both platforms at bench scale, using commercially available basal and feed media, a standard feed strategy for fed-batch and ATF filtration for perfusion. Product concentration in fed-batch is 2.5 times greater than perfusion, while average productivity in perfusion is 7.5 times greater than fed-batch. PCA reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 48 publications
2
47
0
Order By: Relevance
“…In the literature, past studies produced contradictory conclusions on the IgG glycosylation when comparing the two cell culture modes, where some studies demonstrated similarities [9,10] and others showed discrepancies in the IgG glycan structures [13,14]. A recent report of a head-to-head comparison between perfusion and fed-batch cell cultures noted a strong similarity in the IgG glycosylation dynamics [45], an observation that aligns well with the result of our analysis.…”
Section: Discussionsupporting
confidence: 83%
“…In the literature, past studies produced contradictory conclusions on the IgG glycosylation when comparing the two cell culture modes, where some studies demonstrated similarities [9,10] and others showed discrepancies in the IgG glycan structures [13,14]. A recent report of a head-to-head comparison between perfusion and fed-batch cell cultures noted a strong similarity in the IgG glycosylation dynamics [45], an observation that aligns well with the result of our analysis.…”
Section: Discussionsupporting
confidence: 83%
“…The biopharmaceutical industry is following other industries in moving from discrete batch operation to integrated continuous manufacturing, especially for high demand products, such as monoclonal antibodies (MAbs; Shukla, Wolfe, Mostafa, & Norman, 2017; Walsh, 2018). The drivers for continuous processing are many‐fold; process intensification and cost savings (Baur, Angarita, Müller‐Späth, Steinebach, & Morbidelli, 2016; Hummel et al, 2018; Pagkaliwangan, Hummel, Gjoka, Bisschops, & Schofield, 2018; Pollock, Coffman, Ho, & Farid, 2017) might emerge as the most obvious ones but steady‐state operation and thus better, more reproducible quality have also been associated with continuous biomanufacturing (Karst et al, 2017; Kaufman, Wasley, & Dorner, 1988; Walther et al, 2019). While upstream processing is ahead in this transition, where chemostat and perfusion reactors are commonly employed at the manufacturing scale (Arathoon & Birch, 1986; Shukla et al, 2017; Warnock & Al‐Rubeai, 2006), downstream operations have only in recent years started this transition.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps because a significant fraction of cellular energy resources are devoted to continued biomass generation, cells in a continuous sustainable perfusion system may have lower per cell, or specific, productivity (usually measured in pg·cell −1 ·day −1 ) when compared with a less sustainable perfusion process (Gagnon, Nagre, Wang, & Hiller, ), or in the extreme with a fed‐batch process (Bi, Shuttleworth, & Al‐Rubeai, ; Suzuki & Ollis, ). Significant differences have also been noted in the product quality of proteins produced in a sustainable perfusion system compared with that produced from a more traditional fed‐batch operation (Meuwly et al, ; Walther et al, ). In continuous perfusion cultures that maintain a cell culture at minimal growth rates, a constant, low cell bleed rate may also serve to continuously remove accumulated biomass debris resulting mostly from cell death due to some process insult (e.g.…”
Section: Introductionmentioning
confidence: 99%